Evidence-based supportive care in multiple myeloma. Issue 4 (3rd July 2020) - Qureshi, Anum; Tariq, Muhammad Junaid; Shah, Zunairah; Abu Zar, Muhammad; Aslam, Shehroz; Rafae, Abdul; Shafqat, Madeeha; Malik, Mustafa Nadeem; Faisal, Muhammad Salman; Anwer, Faiz
ABSTRACT: Multiple myeloma (MM) is a hematological malignancy characterized by an abnormal clone of plasma cells in the bone marrow. MM and its therapy increase the risk of complications like anemia, osteolytic lesions, pain, infections, and renal abnormalities in MM patients. Supportive care for MM patients improves the quality of life. Treatment with bisphosphonates decreases skeletal-related events. Vertebroplasty and kyphoplasty are done in cases of vertebral compression fractures. Prophylactic antibiotics and antivirals can decrease infections related to morbidity. Plasmapheresis in patients with renal dysfunctions decreases dialysis dependency and improve quality of life.